Suplementasi Keong Mas (Pomacea canaliculata Lamarck) dalam Ransum Berbasis Limbah Restoran dan Ampas Kelapa terhadap Performa Itik Hibrida (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2019)
This research was aimed to evaluate the effect of boiled golden snail (Pomacea canaliculata Lamarck) supplementation on duck diet based on restaurant waste and coconut pulp to duck performance. A total of 80 Mojosari-Peking hybrid ducks 23 days old were reared for 40 days in this study. The treatments diet was as follows: control diet and 3 treatments diet of boiled golden snail supplementation levels of 10%, 15% and 20%. This research used a completely randomized design with 4 treatments and 4 replicates. All data was analyzed by variance and if there were significantly differences, further analysis applied was a Duncan Multiple Range Test. The variables observed were duck performance (feed consumption, body weight gain and feed conversion ratio) and carcass percentage. The results showed that supplementation of boiled golden snail on diet based on restaurant waste and coconut pulp 10%-20% significantly (p